THE CORRELATION BETWEEN PARENTSâ SOCIOECONOMIC CONDITION AND ENGLISH STUDENTS LEARNING ACHIEVEMENT - Warahmah, Mawaddah (Reflective, 2012)
The aims of this study was to investigate The Correlation Between Parentsâ Socioeconomic Condition and English Students Learning Achievement. To what extend socio-economic conditions correlate to students achievement of learning English, how high is the correlation of socioeconomic conditions of parents towards English learning achievement. The objectives to be achieved in this study is to find out to know how the socio-economic conditions of students parents and its correlation on English learning achievement, to determine the correlation level of parents socio-economic background of students who differ on English learning achievement and then to know how high is the correlation of parents socio-economic conditions towards English learning achievement.